(untitled) (Economics and region, 2023)
The economic crisis, provoked by the COVID-19 pandemic and the full-scale invasion of the Russian Federation into Ukraine, made it necessary for companies to find new forms of business management, increase competitiveness, reduce personnel, and optimize costs. Accounting outsourcing, as one of these forms, allows companies to improve the quality of accounting and analytical support and to successfully solve strategic tasks. Outsourcing is used in many technological and logistical processes, marketing, tax consulting, accounting and reporting. The application of accounting outsourcing in Ukraine, although it is rapidly developing, does not correspond to the level of developed countries of the world. Today, accounting outsourcing in Ukraine ranks sixth in the total volume of outsourcing services. The purpose of the work is to study the theoretical and practical principles of evaluating the effectiveness of accounting outsourcing at the enterprise. The criteria for determining the expediency of outsourcing and methodical approaches to evaluating the effectiveness of its application are summarized. In order to determine the peculiarities of the methods of assessing the feasibility of outsourcing, their advantages, disadvantages and the selection of the most optimal of them, calculations were carried out based on the materials of the business entity - the limited liability company of the agricultural firm "ChBG". Calculation of the economic efficiency of accounting outsourcing according to the data of four outsourcing companies showed that all the considered methods are based on the application of only value indicators. When choosing an outsourcer, you should also take into account quality indicators. Each of the methods of evaluating the effectiveness of the use of autosourcing has both advantages and disadvantages, there is no perfect method, which hinders its development in Ukraine.